Effect of thermal ageing on the corrosion behaviour of austenitic stainless steel welds in the simulated PWR primary water. (1st August 2020) - Chen, Junjie; Jang, Changheui; Kong, Byeon Seo; Xiao, Qian; Obulan Subramanian, Gokul; Kim, Ho Sub; Shin, Ji Ho
Highlights: There was significant spinodal decomposition without G-phase after thermal ageing. Thermal ageing does not change the duplex oxide film formation mechanism. Outer oxides of thermally aged ER316L have slightly higher Fe and Ni contents. There was more Ni enrichment in ferrite under M/O interface of aged ER316L. Oxide film on aged ER316L has higher point defect densities and lower EIS resistances. Abstract: The corrosion behaviour of as-welded and thermally aged ER316L in simulated pressurised water reactor (PWR) primary water was studied. Significant spinodal decomposition without G-phase was observed after thermal ageing. Thermal ageing does not change the duplex oxide film formation mechanism on ER316L. Slightly higher Fe and Ni concentrations are in the external oxide particles of thermally aged ER316L. More Ni enrichment is in ferrite of as-welded ER316L beneath the ferrite/inner oxide layer interface. Oxide films of thermally aged ER316L show higher point defect densities and lower EIS resistances.